Role of Social Networking Sites on Depression among Nigerian Young Adults - Omozejele, Humphrey Oseremhen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Social Networking Sites have continued to play significant roles in the transformation of human lives and system. SNS have been ascribed as platforms that causes depression among youth most especially due to the level of its use. Therefore, the overall objective of the study is to find out what acts on social media cause depression among Nigerian Young Adults. Using a qualitative design, this study helps to provide an in-depth understanding of 21 respondents who are Nigerians with regards to their experience in SNS use and depression. The questions were targeted at helping to achieve certain purposes and make useful findings. The study was carried out in Fall 20018, in Lagos, Nigeria. The study used triangulation method in collecting its data (interviews, field notes, and observation) which were analyzed thematically. Findings indicate that SNS platforms contribute to depression among Nigerian youths in many ways. The research has been able to find out that there exists a relationship between the use of SNS and the high level of depression experienced by youth in this generation. In addition, findings have been able to attenuate that SNS though facilitates depression, it has also served as an effective tool in creating awareness or campaigning about the causes of depression among the Nigerian youths.

ÖZ: Sosyal Paylaşım Siteleri, insan hayatlarının dönüşümünde önemli bir rol oynamaya devam etmektedir. Özellikle Sosyal Paylaşım Siteleri, kullanım oranlarından ötürü gençler arasında depresyona yol açan platformlar olarak ayrılmaktadır. Bu çalışmanın amacı Sosyal Paylaşım Siteleri üzerinde hangi davranışların Nijeryalı genç yetişkinler arasında depresyona sebep olduğunu bulmaktadır. Kuramsal çerçevede Kullanımlar ve Doyumlar ve Üçüncü Kişi Etkisi Kuramı kullanılmıştır. Nitel Metot kullanarak bu çalışma, depresyon ve Sosyal Paylaşım Sitesi deneyimleri bakımından Nijeryalı 21 katılımcının anlaşılmasına yardımcı olur. Sorular, kullanışlı bulgular için ve belirti amaçların başarılmasında yardımcı olmayı hedeflemektedir. Çalışma 2018 yaz ayında Lagos, Nijerya’da gerçekleşmiştir. Bu çalışma, konularına göre analiz edilen, veri toplamasında (röportajlar, saha notları ve gözlemler) üçleme metodu kullanılmıştır. Bulgular, Sosyal Paylaşım Platformlarının Nijeryalı gençleri arasında depresyona katkı yaptığını göstermektedir. Ayrıca, bulgular günümüzün neslinde yüksek oranda depresyona giren geçler ve sosyal paylaşım sitesi kullanımı arasında bir ilişki ileri sürmektedir. Buna ilaveten bulgular Sosyal Paylaşım Sitelerinin depresyona olanak sağlamasına rağmen, Nijeryalı gençler arasında depresyon sebeplerine karşı mücadelede ve farkındalık yaratmakta etkili bir araç olarak hizmet etmektedir.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2019. Supervisor: Assoc. Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; Social Media--Communication--Nigerian Students--Eastern Mediterranean University--Cyprus, North; sns; depression; Nigerians; social media; third person; U&G